LEGAL CERTAINTY REGARDING REGULATIONS CONCERNING CORPORATE SOCIAL RESPONSIBILITY IN INDONESIA (STUDY OF LAW NUMBER 40 OF 2007 CONCERNING LIMITED LIABILITY COMPANIES AND LAW NUMBER 25 OF 2007 CONCERNING CAPITAL INVESTMENT) - Ageng Bambang Saputro; Iwan Permadi; Supriyadi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Corporate Social Responsibility obligations for companies as outlined in Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 25 of 2007 concerning Capital Investment create ambiguity due to differences in definitions and terminology used by the Law. The problems in this research are (1) What is the legal ratio for corporate social and environmental responsibility for companies according to the provisions of Law Number 40 of 2007 concerning Limited Liability Companies, (2) What are the implications that arise regarding regulations regarding Corporate Social Responsibilityin Indonesia. This research uses a normative juridical research method with a conceptual approach and a statutory approach. Data collection techniques were carried out by means of literature study. The results of the research state that (1) Ratio Legis according to the Limited Liability Company Law is a philosophical basis, corporate social responsibility is a concrete form of effort to provide welfare to society. The sociological basis of the Company is a capital company established on the basis of a commercial performance agreement (2)CSR regulations are unclear and overlap with other related laws and regulations. Not all companies related to natural resources have implemented social and environmental responsibility, because there is still a perception that sharing social responsibility is not mandatory and there is a lack of good government control and strict sanctions to enforce it.